KAJIAN EFEKTIVITAS PENGGUNAAN PRIVATE LABEL UNTUK MENINGKATKAN PENJUALAN TOKO/RITEL - Maria Agus Tina (Kompetensi (Competence : Journal of Management Studies), 2017)
Indonesian retail business has been growing with the increase in the numberof retailers that exist. A growing business competition is currently making retail companies expand through private label. Private label is a brand of products sold by using the name of the store. Private label is one of retailer’s strategy to be competitive in the market. Effective use of private label can make consumers interested in buying and using private label productsif retailers can build confidence in private label products that they have. Product with a good quality will make consumers believe, the attractive packaging will make consumers want to use or purchase the products and the price becomes the deciding factor of the success of private label. Low prices of private label will make consumers choose to buy it, but the low prices can make perception that product also lower quality. This article discusses about advantages and disadvantages of private label at store.